(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The GPS allows locating an object in any part of the World with a certain degree of accuracy. Some precision activities need to operate with a sub-metric level of accuracy. This paper introduces a data analysis tool to process the GPS information, by applying filters and algorithms to obtain a more precise position. The experimental results can achieve a positional accuracy of Â± 1.00 meter. Â